Hoffmannia rzedowskiana (Rubiaceae), a new species of southern Mexico and Nicaragua - Castillo-Campos, Gonzalo; Bautista Bello, Alma Patricia; Lorence, David H. (Instituto de Ecología, A.C., 2014)
Hoffmannia rzedowskiana Cast.-Campos, Bautista-Bello and Lorence (Rubiaceae) is described and illustrated as a new species from southern Mexico (Chiapas, Oaxaca and Veracruz) and Nicaragua. In Veracruz, it occurs in the region of Los Tuxtlas and Uxpanapa near the border with the Chimalapas (Oaxaca). This species is related to Hoffmannia discolor, from which it differs by presenting leaves which are pilose on the abaxial surface, sessile to shortly petiolate, lateral veins 19-23(-26) pairs, pubescent flowers and a linear stigma.